إدارة الجودة الشاملة للتعلم المدمج في التعليم العالي )مدخل نظري( - المدرس الدكتور احمد عبد عون عبد علي; المدرس غسان علي عاصم (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Education is one of the most important cultural features of the peoples and many countries still harness their resources for the development of education and upgrading them towards the best ways to build the individual and society and thus achieve the highest goals of the institution. The Blended Learning is one of the most important features of the era of electronic development, including the use of new technologies that are growing rapidly and increasing, which combines the traditional theory of learning and the theory of active learning, and no doubt that the research also took a rapid pace to pursue the progressive development in education, E-learning The importance of learning integrated into the integration of several types of education in one place according to models tried and determined and set the necessary standards for success taking into account the high material costs associated with this learning strategy and also the difficulty of implementation Some models are being targeted, trained, trained and trained. The aim of this study was to define the integrated learning method, its models, its functional methods, the most appropriate educational designs for the application in higher education, and the definition of the concept of "TQM "for higher education with the quality of the input outputs for the educational process and the monitoring of the performance in order to achieve the vision and mission of the universities. A TQM model for Blended Learning has been proposed and is being to tested by other researchers with the theoretical conviction of the flexibility and simplicity factor the model is created and named as (TQMBL360) The study showed (theoretically) the existence of several factors that help the model to acquire the form of Jah of which provide technological and economic environment, family and labor market, calendar, and the existence of moral society and the environment to integrate with the objectives of the Higher Corporation.